(untitled) (The Science Post, 2025)
Heart disease remains the foremost cause of mortality worldwide, despite advances in clinical interventions. Recent technological innovations offer transformative potential in the prevention, diagnosis, and management of cardiovascular diseases (CVDs). From wearable technologies that enable real-time monitoring to artificial intelligence (AI) systems that enhance diagnostic accuracy and digital health platforms that improve patient access and compliance, technology is reshaping the landscape of cardiology. This paper explores how these tools are currently deployed in clinical practice, their implications for healthcare delivery, and the challenges that must be addressed to fully realize their benefits. By examining both current applications and future possibilities, the paper underscores the pivotal role of technology in mitigating the global burden of heart disease.